2019
DOI: 10.3390/mi10120830
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Microfluidics: Fundamentals, Recent Developments, and Applications

Abstract: Miniaturization has been the driving force of scientific and technological advances over recent decades. Recently, flexibility has gained significant interest, particularly in miniaturization approaches for biomedical devices, wearable sensing technologies, and drug delivery. Flexible microfluidics is an emerging area that impacts upon a range of research areas including chemistry, electronics, biology, and medicine. Various materials with flexibility and stretchability have been used in flexible microfluidics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 190 publications
1
100
0
Order By: Relevance
“…Microfluidics as a contemporary technology offers a multitude of application possibilities by manipulating fluids in microchannels and is becoming increasingly important not only in point-of-care testing, analysis, biotechnology, and chemistry but above all for the formulation of NP-based pharmaceuticals and personalized medicine [ 18 , 19 ]. Nowadays, reams of microfluidic chips are available with all kinds of geometries that control the fluids and the mixing of fluids either actively or in a passive manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics as a contemporary technology offers a multitude of application possibilities by manipulating fluids in microchannels and is becoming increasingly important not only in point-of-care testing, analysis, biotechnology, and chemistry but above all for the formulation of NP-based pharmaceuticals and personalized medicine [ 18 , 19 ]. Nowadays, reams of microfluidic chips are available with all kinds of geometries that control the fluids and the mixing of fluids either actively or in a passive manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies found in microfluidic platforms, living cells can be cultured while nutrients continue to be released [33]. However, it suffers from incapability for large-scale culture, even though it is convenient for drug delivery testing [34].…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidics have been classically defined as systems that manipulate and interrogate sub-microliter volumes (μL) of fluid within engineered structures of critical lengths less than 1000 microns (μm), or 1 millimeter (mm) [ 20 ]. This multidisciplinary field has fused key principles of physics and surface chemistry [ 21 , 22 , 23 ] with engineering processes of microfabrication [ 24 , 25 ] to create precisely-controlled systems on the scale of biological cells and anatomical structures [ 23 , 25 , 26 ]. Physical phenomena that dominate fluid behaviors at the microscale are distinct, and induce fluid responses that are significantly different from those classically-observed at the macroscale, i.e., with millimeter dimensions and above [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%